Three Napoleonic battles - Parker, Harold Talbot, 1907- (e-Duke books scholarly collection., 1983)
Three Napoleonic Battles not only describes important engagements of the French imperial era but also offers valuable insights into the nature of battle. This new edition of Professor Parker's work will thus be of interest to both Napoleonic and military historians who will find it in the forefront of current military scholarship.